2018
DOI: 10.1088/1361-6528/aab936
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of surfactant-free Au NPs/RGO/Ni foam for degradation of 4-nitrophenol and detection of hydrogen peroxide

Abstract: The application of Au nanoparticles (Au NPs) often requires surface modification with chemical surfactants, which dramatically reduce the surface activity and increase the chemical contamination and cost of Au NPs. In this research, we have developed a novel Au NPs/reduced graphene oxide/Ni foam hybrid (Au NPs/RGO/NiF) by in situ reduction through ascorbic acid and replacement reaction. This method is green, facile and efficient. The Au NPs are free of chemical surfactants and are homogeneously distributed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In particular, gold nanoparticles or nanoclusters (Au NPs/NCs) exhibit excellent peroxidase-mimicking activity, good biocompatibility, and flexible modification on the surface . However, as Au NPs/NCs tend to aggregate easily due to the high surface energy, the prepared Au NPs/NCs require the protection of ligands or capping agents like macromolecules. , Usually, the catalytic reaction takes place on the surface, and the coating ligands used to protect Au NPs/NCs may block certain active sites on the surface, further reducing the catalytic activity. Besides, previous studies have shown that the catalytic activity of Au NPs/NCs is correlated with size, and the smaller the size, the more the active sites are generally exposed, and potentially higher the catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gold nanoparticles or nanoclusters (Au NPs/NCs) exhibit excellent peroxidase-mimicking activity, good biocompatibility, and flexible modification on the surface . However, as Au NPs/NCs tend to aggregate easily due to the high surface energy, the prepared Au NPs/NCs require the protection of ligands or capping agents like macromolecules. , Usually, the catalytic reaction takes place on the surface, and the coating ligands used to protect Au NPs/NCs may block certain active sites on the surface, further reducing the catalytic activity. Besides, previous studies have shown that the catalytic activity of Au NPs/NCs is correlated with size, and the smaller the size, the more the active sites are generally exposed, and potentially higher the catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (Au NPs) with sizes between 1 and 100 nm have received tremendous attention due to their remarkable catalytic, electronic, and magnetic activities, which make them attractive targets for various applications. Their application in catalytic reduction of oragnic dyes to inactive substance is significant important because most of organic dyes are carcinogenic and very low concentration in water will cause health-risk problems . While Au NPs contain many active sites that enhance their catalytic activity compared with bulk Au, the high surface energy of Au NPs often leads to aggregation, which greatly reduces their catalytic efficiency. To improve the stability of Au NPs catalysts, various substrates such as carbon materials, silica materials, metal–organic frameworks, metal oxides, metal hydroxides, clay, and polymers have been used to immobilize Au NPs on their surfaces. Among these materials, graphene oxide (GO) has been shown to be a highly efficient carbon support for fabricating GO@Au NPs nanocomposites. , Its large specific surface area and structural defects in its lattice provide abundant reactive sites to bind and support many Au NPs. These properties increase the electrical conductivity and electrical transfer of the catalyst, thus increasing its catalytic activity toward organic contaminants .…”
Section: Introductionmentioning
confidence: 99%
“…As a proof of concept, we evaluated our paper-based electrode (patterned with Au NPs/rGO/cellulose regions) for the electrochemical analysis using the commonly studied analyte H 2 O 2 . In our initial study, we added a drop of H 2 O 2 -containing phosphate-buffered solution (PBS, pH 7) to our electrode and performed CV measurements, as shown in Figure a. The CV response for one electrode shows a systematic increase in current with liquid drops containing increasing levels of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Selectivity was assessed using (d) common interfering compounds and (e) a complex background matrix (i.e., milk). (f) Comparison of the performance of our paper-based electrode for H 2 O 2 detection (LOD is the limit of detection). …”
Section: Resultsmentioning
confidence: 99%